Delayed return of gastrointestinal function after hepatectomy in an ERAS program: incidence and risk factors. Issue 9 (September 2022) - Arfa, Sara; Turco, Célia; Lakkis, Zaher; Bourgeois, Sandrine; Fouet, Isabelle; Evrard, Philippe; Sennegon, Elise; Roucoux, Alexandra; Paquette, Brice; Devaux, Bénédicte; Rietsch-Koenig, Anne; Heyd, Bruno; et al.
Abstract: Background: Delayed return of gastrointestinal function (DGIF) after hepatectomy can involve increased morbidity and prolonged hospital stay. Yet, data on incidence and risks factors are lacking. Methods: All consecutive patients who underwent hepatectomy between June 2018 and December 2020 were included. All patients were included in an enhanced recovery after surgery (ERAS) program. DGIF was defined by the need for nasogastric tube (NGT) insertion after surgery. DGIF risk factors were identified. Results: Overall, 206 patients underwent hepatectomy. DGIF occurred in 41 patients (19.9%) after a median time of 2 days (range, 1–14). Among them, 6 patients (14.6%) developed aspiration pneumonia, of which one required ICU for mechanical ventilation. DGIF developed along with an intraabdominal complication in 7 patients (biliary fistula, n = 5; anastomotic fistula, n = 1; adhesive small bowel obstruction, n = 1). DGIF was associated with significantly increased severe morbidity rate (p = 0.001), prolonged time to normal food intake (p < 0.001) and hospital stay (p < 0.001) and significantly decreased overall compliance rate (p = 0.001). Independent risk factors of DGIF were age (p < 0.001), vascular reconstruction (p = 0.007), anaesthetic induction using volatiles (p = 0.003) and epidural analgesia (p = 0.004). Using these 4 variables, a simple DGIF risk score has been developed allowing patient stratification in low-, intermediate- and high-risk groups. Conclusion: DGIF after hepatectomy was frequently observed and significantly impacted postoperative outcomes. Identifying risk factors remains critical for preventing its occurrence. Graphical abstract: Image 1